A survey of risk factors associated with hypertension in the adult population of Kang, Kgalagadi North, Botswana - S. Tshitenge; L. H. Mabuza (South African Family Practice)
Background: Sustainable and aggressive population-based programmes on hypertension awareness, prevention, treatment and control are key to the successful control of this epidemic. The objective of the study was to determine to what extent hypertension and risk factors for its development were prevalent in the Kang village community in Botswana, and specifically to assess its prevalence in the adult population and its relationship with high blood pressure, anthropometric measures and lifestyle factors, i.e. diet and the use of tobacco products and alcohol.